TP6.2.7 Routine examination of gallbladder specimens after cholecystectomy: a single-centre analysis of the incidence, clinical and histopathological aspects of incidental gallbladder carcinoma. (28th October 2021) - Mauro, David Di; Orabi, Amira; Myintmo, Aye; Reece-Smith, Alex; Wajed, Shahjehan; Manzelli, Antonio
Abstract: Aims: Gallbladder carcinoma is often found incidentally on histopathologic examination after cholecystectomy – this is referred as incidental gallbladder carcinoma (IGC). Routine vs selective histopathological assessment of gallbladders is under debate, this study evaluates the role of regular specimens' examination, based on a single-centre analysis of incidence, clinical and histopathological aspects of IGC. Methods: Patients who underwent cholecystectomy, between July 2010 and January 2020, were considered. Exclusion criteria were age under 18 and preoperative diagnosis of GB carcinoma. Demographic, clinical and histopathological data were retrospectively collected, continuous variables with a normal distribution were evaluated with Student's t-Test and ANOVA. Results: Some 5779 patients were included. The female/male ratio was 2.5:1. Chronic cholecystitis (CC) was the most common finding on specimens (99.3%), IGC was found in 6 cases (0.1%). In the latter group, there were 5 women and patients were older than those with benign disease – 73.7 ± 5.38 years vs 55.8 ± 0.79 years (p < 0.05). In all the cases, the GB was abnormal on intraoperative inspection and beside cancer, histopathology showed associated CC and/or dysplasia. Upon diagnosis, disease was at advanced stage – one stage II, one stage IIIA, one stage IIIB, three stage IVA. Two patients are alive, three died of disease progression – median survival was 7 months (range 2-14). Conclusions: In this series, ICG was rare, occurred most commonly in old adult women and was diagnosed at an advanced stage. In all the cases, the GB was abnormal intraoperatively, therefore macroscopic GB anomalies demand histopathological assessment of the specimen.